Colchicine Impacts Leukocyte Trafficking in Atherosclerosis and Reduces Vascular Inflammation - Meyer-Lindemann, Ulrike; Mauersberger, Carina; Schmidt, Anna-Christina; Moggio, Aldo; Hinterdobler, Julia; Li, Xinghai; Khangholi, David; Hettwer, Jan; Gräßer, Christian; Dutsch, Alexander; Schunkert, Heribert; Kessler, Thorsten; et al. (Frontiers in Immunology, 2022)
Background: Inflammation strongly contributes to atherosclerosis initiation and progression. Consequently, recent clinical trials pharmacologically targeted vascular inflammation to decrease the incidence of atherosclerosis-related complications. Colchicine, a microtubule inhibitor with anti-inflammatory properties, reduced cardiovascular events in patients with recent acute coronary syndrome and chronic coronary disease. However, the biological basis of these observations remains elusive. We sought to explore the mechanism by which colchicine beneficially alters the course of atherosclerosis. Methods&Results: In mice with early atherosclerosis (Apoe-/- mice on a high cholesterol diet for 8 weeks), we found that colchicine treatment (0.25 mg/kg bodyweight once daily over four weeks) reduced numbers of neutrophils, inflammatory monocytes and macrophages inside atherosclerotic aortas using flow cytometry and immunohistochemistry. Consequently, colchicine treatment resulted in a less inflammatory plaque composition and reduced plaque size. We next investigated how colchicine prevented plaque leukocyte expansion and found that colchicine treatment mitigated recruitment of blood neutrophils and inflammatory monocytes to plaques as revealed by adoptive transfer experiments. Causally, we found that colchicine reduced levels of both leukocyte adhesion molecules and receptors for leukocyte chemoattractants on blood neutrophils and monocytes. Further experiments showed that colchicine treatment reduced vascular inflammation also in post-myocardial infarction accelerated atherosclerosis through similar mechanisms as documented in early atherosclerosis. When we examined whether colchicine also decreased numbers of macrophages inside atherosclerotic plaques by impacting monocyte/macrophage transitioning or in-situ proliferation of macrophages, we report that colchicine treatment did not influence macrophage precursor differentiation or macrophage proliferation using cell culture experiments with bone marrow derived macrophages. Conclusions: Our data reveal that colchicine prevents expansion of plaque inflammatory leukocytes through lowering recruitment of blood myeloid cells to plaques. These data provide novel mechanistic clues on the beneficial effects of colchicine in the treatment of atherosclerosis and may inform future anti-inflammatory interventions in patients at risk.